Interface between Education and Tourism around Panchmul Area of Aandhikhola Rural Municipality of Syangja District - Pasa, Rajan Binayek (Dhaulagiri Journal of Sociology and Anthropology, 2021)
This study explores the interface between education and tourism constructs through a qualitative approach and multiple case study research methods. The key objectives of the research were to look at the interface between informal education and tourism, to appraise the interface between non-formal education and tourism as well as to explore the interface between formal education and tourism development activities in the study area. In-depth interviews of 6 males and 3 females from the education program and another 6 males and 3 females from the tourism development program were undertaken by applying the purposive sampling principle. Likewise, 3 FGDs and participant observation techniques were also applied for developing multiple forms of genres, which were generated through re/productive socio-cultural and economic structures of Panchmul. The findings reveal that education plays a functional transformative role in tourism development that is supported by the theory of practice, capability approach, and sustainability approach. Based on the findings, this study has also developed a strategic interface model and strategic framework for tourism development that can be applied in the Panchmularea and other similar places. Hence, knowledge generated from this study is equally fruitful to readers, local development stakeholders, and policymakers and planners in central, provincial, and local levels of governments in Nepal.